'People and their homes rather than housing in the usual sense'? Locating the tenant's voice in Homes in High Flats. Issue 5 (29th July 2019) - Hazley, Barry; Wright, Valerie; Abrams, Lynn; Kearns, Ade
ABSTRACT: In recent years, the social research of Pearl Jephcott has been subject to scholarly reappraisal on the grounds that it displays an early commitment to the unmediated reporting of 'the authentic voice of her participants'. This article investigates the extent to which this claim holds for Jephcott's seminal 1971 study Homes in High Flats . It suggests that, although Homes in High Flats sought to investigate 'people and their homes rather than housing in the usual sense', the study's ability to realise this aim was complicated by the social distance obtaining between researcher and researched. Based on re-analysis of the study's archived research materials, the article explores how this distance mediated the researchers' interpretation and re-presentation of the tenant's voice, deepening understanding of the epistemological premises of Jephcott's work.